A tale of two cities - Dickens, Charles, 1812-1870 (Delhi : Global Media, 2007)
The inhabitants of two cities--including a doctor, his devoted daughter, the young French aristocrat she loves, and their English friend--are swept into the tide of the French Revolution
Title from container
System requirements: Window 95/98/ME/2000/NT/XP/Vista ; 16 MB RAM or greater ; CD-ROM drive 4x or greater Pentium PC or higher ; 16 bit sound card ; 50 MB available HD space ; 256 colour VGA monitor or greater ; Macromedia Flash Player ; Adobe Acrobat Reader
Keywords: France -- History -- Revolution, 1789-1799; Paris (France) -- History -- 1789-1799 -- Fiction; London (England) -- History -- 18th century -- Fiction